A wideband noise cancelling balun LNA employing current reuse technique. (June 2018) - Eskandari, R.; Ebrahimi, A.; Sobhi, J.
Abstract: A balun inductorless wideband low noise amplifier (LNA) with active loads is proposed for multi-standard radio applications. The noise cancelling and current reuse techniques are combined to mitigate the need for high power consumption in conventional balun LNAs. This adds a degree of freedom for transconductance of common gate stage (g mCG ). As a result, lower g mCG without degrading the input matching, allows a large scaling factor for common source (CS) stage in noise cancelling technique. Post-layout simulation results of the proposed LNA circuit in a 180 nm RF CMOS process show voltage gain of 20.2 dB, −3 dB bandwidth from 600 MHz to 3.15 GHz. The minimum NF is 2.37 dB with input return loss (S11 ) better than −13 dB in all frequency range and third input intercept point (IIP3 ) is −2.1 dBm. The circuit dissipates 6 mW from 1.5 V DC supply with an active area of 0.026 mm 2 .